2022
DOI: 10.1007/s10974-022-09622-4
|View full text |Cite
|
Sign up to set email alerts
|

Myosin assembly of smooth muscle: from ribbons and side polarity to a row polar helical model

Abstract: After decades of debate over the structure of smooth muscle myosin filaments, it is still unclear whether they are helical, as in all other muscle types, or square in shape. In both cases bipolar building units are proposed, but the deduced cross-bridge arrangements are fundamentally different. The opposite polarity of the adjusting longitudinal rows is proposed for the helical structure, while in the case of square filaments, or myosin ribbons, only their two faces are appositively polarized. Analysis of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Further complexity could also arise from heterogenous myosin 2 subcellular functions within SMCs, as recent evidence demonstrated unique subcellular localization for SM2 and NM2 in freshly isolated primary cells (35). Finally, while the structure of NM2 bipolar filaments in cells is relatively well-established, the precise structural features of SM2 filaments in intact cells and tissues remains an active area of debate (36). Future studies to dissect unique and common biophysical properties of SM2 and NM2 filaments in SMCs should prove insightful.…”
Section: Discussionmentioning
confidence: 99%
“…Further complexity could also arise from heterogenous myosin 2 subcellular functions within SMCs, as recent evidence demonstrated unique subcellular localization for SM2 and NM2 in freshly isolated primary cells (35). Finally, while the structure of NM2 bipolar filaments in cells is relatively well-established, the precise structural features of SM2 filaments in intact cells and tissues remains an active area of debate (36). Future studies to dissect unique and common biophysical properties of SM2 and NM2 filaments in SMCs should prove insightful.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally shown that the solubilized smooth muscle myosin molecule may adopt one of two possible configurations: the folded one (a loop) being more soluble, or the extended (straight) one, less soluble, aggregating to dimers and tetramers [15,16]. Such tetramers are associated with coiled-coil rods, forming what is considered in vivo the myosin filament-building units [17].…”
Section: Introductionmentioning
confidence: 99%